2017
DOI: 10.4236/ojvm.2017.711016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Time on Cauda Epididymal Sperm Parameters of Nigerian Local Dogs

Abstract: Aim: Storage of testes-epididymides at refrigeration temperature is a promising method of short-term sperm preservation for use in reproductive biotechnology in dogs. This study aimed to determine the effect of storage time at 4˚C on the quality of Nigerian local dogs' cauda epididymal spermatozoa recovered post-castration. Materials and Methods: Testes along with their epididymides collected immediately after castration of local dogs were either processed immediately (0th hour) or stored at 4˚C in the refrige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The percentage motility and viability of cauda epididymal spermatozoa observed in this study for the N groups were comparable to the values reported previously in normal dogs (Chima et al, 2017;Bhanmeechao et al, 2018). Testicular degeneration decreased the epididymal sperm total and progressive motility in the D group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The percentage motility and viability of cauda epididymal spermatozoa observed in this study for the N groups were comparable to the values reported previously in normal dogs (Chima et al, 2017;Bhanmeechao et al, 2018). Testicular degeneration decreased the epididymal sperm total and progressive motility in the D group.…”
Section: Discussionsupporting
confidence: 90%
“…Spermatozoa can be recovered from the cauda epididymis of dogs by percutaneous epididymal aspiration, following castration, or at post mortem; for use in the investigation of sperm quality and spermatozoal characteristics (Varesi et al, 2013;Chima et al, 2017;Bhanmeechao et al, 2018), and for artificial breeding of bitches (Wydooghe et al, 2016). Ejaculated semen comprises sperm from both testes as well as secretions of the accessory sex glands.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm reserves have been evaluated from slaughtered domestic animals [ 9 ], while sperm quality parameters have been evaluated from sperm recovered from the cauda epididymis of recently slaughtered animals [ 10 , 11 ]. The recovery of spermatozoa from the epididymides of recently dead or slaughtered valuable animals ensures the preservation of genetic material for future use [ 12 ]. Scarce information is available on the correlation of testicular morphometric parameters with sperm reserves, particularly in West African Dwarf rams in Ghana.…”
Section: Introductionmentioning
confidence: 99%